Promotional Media Design for Bank Sampah ‘Wani’ - Salsabiil Azzahra; Irhamna Nirbhaya Carecca (Journal of Creative Industries and Vocational Innovation, 2025)
This research stems from the need for effective visual promotional media in the digital era to strengthen institutional identity and broaden public outreach. To support this, Bank Sampah Wani Surabaya requires media that can communicate information clearly and engagingly. A qualitative approach was used in this study, with data collected through interviews and direct observation. The design resulted in several promotional outputs, including two videos: one profile video and one educational video on waste management, each with a maximum duration of five minutes, as well as a printed product catalog. These media are intended to support outreach activities such as school roadshows, environmental campaigns, and online distribution. The final outcomes are expected to help fulfill the communication needs of Bank Sampah Wani and raise greater awareness about sustainable waste management among the public.